A prospective clinical cohort study of women at increased risk for endometrial cancer - Clarke, Megan A.; Long, Beverly J.; Sherman, Mark E.; Lemens, Maureen A.; Podratz, Karl C.; Hopkins, Matthew R.; Ahlberg, Lisa J.; Mc Guire, Lois J.; Laughlin-Tommaso, Shannon K.; Wentzensen, Nicolas; Bakkum-Gamez, Jamie N. (Gynecologic oncology, 2020)
To evaluate endometrial cancer (EC) risk assessment and early detection strategies in high-risk populations, we designed a large, prospective cohort study of women undergoing endometrial evaluation to assess risk factors and collect novel biospecimens for future testing of emerging EC biomarkers. Here we report on the baseline findings of this study. Women aged ≥45 years were enrolled at the Mayo Clinic from February 2013–June 2018. Risk factors included age, body mass index (BMI), smoking, oral contraceptive and hormone therapy use, and parity. We collected vaginal tampons, endometrial biopsies, and Tao brush samples. We estimated mutually-adjusted odds ratios (OR) and 95% confidence intervals (CI) using multinomial logistic regression; outcomes included EC, atypical hyperplasia, hyperplasia without atypia, disordered proliferative endometrium, and polyps, versus normal endometrium. Subjects included 1205 women with a mean age of 55 years; 55% were postmenopausal, and 90% had abnormal uterine bleeding. The prevalence of EC was 4.1% (n = 49), predominantly diagnosed in postmenopausal women (85.7%). Tampons and Tao brushings were obtained from 99% and 68% of women, respectively. Age (OR 1.14, 95% CI 1.1–1.2) and BMI (OR 1.39, 95% CI 1.1–1.7) were positively associated with EC; atypical hyperplasia (OR 1.07, 95% CI 1.0–1.1; OR 2.00, 95% CI 1.5–2.6, respectively), and polyps (OR 1.06, 95% CI 1.0–1.1; OR 1.17, 95% CI 1.0–1.3, respectively); hormone therapy use and smoking were inversely associated with EC (OR 0.42, 95%, 0.2–0.9; OR 0.43, 95% CI, 0.2–0.9, respectively). Parity and past oral contraception use were not associated with EC. Well-established EC risk factors may have less discriminatory accuracy in high-risk populations. Future analyses will integrate risk factor assessment with biomarker testing for EC detection. •This large clinical prospective cohort study evaluates risk factors for endometrial cancer and its precursors.•Vaginal tampons, endometrial biopsies, and Tao brushes were collected for future testing of emerging biomarkers.•Of the 1205 participants, 90% had abnormal uterine bleeding and the prevalence of endometrial cancer was 4.1% (n = 49).•Endometrial cancer and benign uterine conditions (e.g., polyps) shared risk factors such as age and body mass index.•Parity and oral contraception use were not associated with endometrial cancer risk in this high-risk population.